2010
DOI: 10.1136/bjo.2009.178889
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life measures (HRQoL) in patients with amblyopia and strabismus: a systematic review

Abstract: Background/aims Health-related quality of life (HRQoL) measures are used in healthcare to help inform clinical decision-making and policy-making decisions. A number of disease-specific or condition-specific measures have been developed and applied in ophthalmology; however, their use in the specific fields of amblyopia and strabismus are not as established. The purpose of this study is to identify and discuss specific HRQoL instruments that may be used in the investigation and management of patients with ambly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 29 publications
(22 reference statements)
0
32
0
1
Order By: Relevance
“…Therefore, measurement of QoL does not need to be confined to research, but should be encouraged in everyday practice to allow for the appropriate and timely discussion about the impact of the condition on patients and also for the prescription of treatment. 8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, measurement of QoL does not need to be confined to research, but should be encouraged in everyday practice to allow for the appropriate and timely discussion about the impact of the condition on patients and also for the prescription of treatment. 8 …”
mentioning
confidence: 99%
“…Strabismus-specific QoL questionnaires cover more comprehensively the range of problems faced by individuals with the condition. Carlton et al 8 identified four strabismus-and amblyopia-specific QoL questionnaires: the amblyopia and strabismus questionnaire 46 (A&SQ), the amblyopia treatment index, 11 the adult strabismus questionnaire [19][20], and the intermittent exotropia questionnaire. 22 The two strabismusspecific questionnaires, the A&SQ and AS-20, have both been shown to have better discriminatory ability when compared with the SF-12 and VFQ-25 18,46 for those with strabismus.…”
mentioning
confidence: 99%
“…The other questionnaires, such as the Amblyopia and Strabismus Questionnaire (A&SQ), the Amblyopia Treatment Index (ATI), and the Intermittent Exotropia Questionnaire (IXTQ), can be the subject of future studies about HRQOL in the Iranian patients. 17 In conclusion, to our knowledge, our study was the first study that developed a Persian version, one of the few studies that developed non-English versions for AS-20, and one of the few studies that evaluated postsurgical HRQOL in the strabismus cases. Our version had good reliability and validity and might be appropriate for evaluating HRQOL in Iranian patients with strabismus.…”
mentioning
confidence: 89%
“…[1][2][3][4][5][6][7][8] Moreover, it has been shown that strabismus negatively affects quality of life in adulthood and surgical intervention improves the quality of life. 9,10 The prevalence of strabismus ranges from less than 0.5% to about 5% in different communities and countries. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the prevalence is substantially higher in some diseases, such as Down or Marfan syndrome.…”
Section: Introductionmentioning
confidence: 99%